2014
DOI: 10.1007/s35834-014-0111-y
|View full text |Cite
|
Sign up to set email alerts
|

Frauen in MINT-Berufen: Retrospektive Wahrnehmung des mathematisch-naturwissenschaftlichen Unterrichts auf der Sekundarstufe I

Abstract: Zusammenfassung Der Beitrag fokussiert die Bedeutung des mathematisch-naturwissenschaftlichen Unterrichts für die Überwindung der geschlechtsbezogenen Disparitäten bei der Berufswahl im Bereich von Mathematik, Informatik, Naturwissenschaft und Technik (MINT). Basierend auf der Annahme, dass in der motivationsförderlichen Gestaltung des Unterrichts ein wirksamer Ansatz zur Reduktion der beharrenden Unterrepräsentation von Frauen in MINT-Berufen liegt, wird der Frage nachgegangen, wie junge Frauen mit einer für … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
5
0
3
Order By: Relevance
“…Since we did not control for other potential determinants in the explanatory models (e.g., self-image of students, their abilities, or interest in science), our results are limited to the investigation of the impact of gender-science stereotype on students' aspirations. It has been demonstrated that further school-related factors, such as the instructional design of science classes (Aeschlimann et al, 2016), teachers' support and encouragement (Aeschlimann et al, 2015) as well as family-related factors, and also peers can considerably influence the career-choice decisions of young people (Makarova et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Since we did not control for other potential determinants in the explanatory models (e.g., self-image of students, their abilities, or interest in science), our results are limited to the investigation of the impact of gender-science stereotype on students' aspirations. It has been demonstrated that further school-related factors, such as the instructional design of science classes (Aeschlimann et al, 2016), teachers' support and encouragement (Aeschlimann et al, 2015) as well as family-related factors, and also peers can considerably influence the career-choice decisions of young people (Makarova et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, it is conceivable that the observed group differences could have existed in students already prior to starting a teacher education. Regarding aspects of motivational orientations, it has already been empirically demonstrated that these represent decisive factors in the choice of study subjects (Aeschlimann et al, 2015;Nagy, 2005;Oepke & Eberle, 2014;Schnabel & Gruehn, 2000). In particular, it has repeatedly been shown that a more distinct educational interest is associated significantly less with the choice of natural science subjects (e.g., Schmidt & Herzer, 2006;Schnabel & Gruehn, 2000).…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…This assumption is in line with a longitudinal causality study by Blömeke et al (2014) who showed that preservice teachers' PCK causally influences their later beliefs, not the other way round. Moreover, potential baseline differences in professional knowledge are particularly contradicted by the fact that it has been shown several times that the two specialized courses taken in the last section of school education-as well as the later university study subjects-are primarily chosen on the basis of motivational orientations (Aeschlimann et al, 2015;Nagy, 2005;Oepke & Eberle, 2014;Schnabel & Gruehn, 2000). Accordingly, it is not surprising that there is a high degree of congruency between the selected specialized courses and later study subjects (e.g., Berweger et al, 2015;Nagy et al, 2006;Puderbach, 2012;Schnabel & Gruehn, 2000).…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…The interviews were conducted by telephone in spring 2012. The selective sample comprised women in the following professional fields: technology and engineering (N = 42, 59 %, e.g., draftswoman) informatics (N = 18, 26 %, e.g., computer scientist), mechanical professions (N = 8, 11 %, e.g., automation engineer), and construction (N = 3, 4 %, e.g., carpenter) (Aeschlimann et al 2015a). The four fields have a much smaller proportion of women than many other STEM fields.…”
Section: Participants and Datamentioning
confidence: 99%